(3GdQbGHI GdeGdjI aj GdCbWGQ GdYQHjIs ((3HjQhJ(B;(3eQcR OQGSGJ GdhMOI GdYQHjI(B:s (3GdefXeI GdYQHjI decGaMI GdaSGO(B,s, 2009)
(3GdQbGHI GdeGdjI GdaGYdI Ydi eGdjI GdOhd GdYQHjI aj Xd NUhUjGJ GdChVGY GdOhdjI hGdEbdjejI(B- (3GdfXGe GdeGdj ddMcheI hOhQg aj aGYdjI GdQbGHI GdeGdjI hecGaMI GdaSGO(B- (3hGbY GdQbGHI GdeGdjI aj dHfGf(B- (3hGbY GdQbGHI GdeGdjI aj eUQ(B- (3hGbY GdQbGHI GdeGdjI aj Gdjef(B- (3hGbY GdQbGHI GdeGdjI aj GdeZQH(B- (3hGbY GdQbGHI GdeGdjI aj GdGQOf(B- (3OhQ GdSdWI GdbVGFjI aj OYe Yed CLgRI GdQbGHI GdeGdjI(B- (3GSJbdGdjI CLgRI GdQbGHI GdeGdjI hYOe GNVGYgG ddeDKQGJ GdSjGSjI GdVGef GdCSGSj daGYdjJgG aj COGA egGegG(B- (3GdQbGHI GdHQdeGfjI Ydi GdSdWI GdJfajPjI hOhQgG GdeMhQj aj OYe aYGdjI GdQbGHI GdeGdjI aj CbWGQ GdhWf GdYQHj(B- (3JMSjf COGA GdQbGHI GdeGdjI aj GdGbWGQ GdYQHjI dHfGf, eUQ, Gdjef, GdeZQH, GdGQOfs
Keywords: (3GdCbWGQ GdYQHjIs; (3GdQbGHI GdeGdjIs; (3JObjb GdMSGHGJs